2017
DOI: 10.2147/cia.s141148
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tongue strength, lip strength, and nutrition-related sarcopenia in older rehabilitation inpatients: a cross-sectional study

Abstract: ObjectiveThe objective of this study was to clarify the relationship between tongue strength, lip strength, and nutrition-related sarcopenia (NRS).Patients and methodsA total of 201 older inpatients aged ≥65 years (70 men, median age: 84 years, interquartile range: 79–89 years) consecutively admitted for rehabilitation were included in this cross-sectional study. The main factors evaluated were the presence of NRS diagnosed by malnutrition using the Mini-Nutrition Assessment – Short Form, sarcopenia based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 47 publications
2
36
0
2
Order By: Relevance
“…The prevalence of reduced muscle mass was described only by one study which reported a reduced SMMI (women < 5.4 kg/m 2 , men < 7.0 kg/m 2 ) in 42.3% of women and 57.7% of men [63]. The prevalence of sarcopenia was reported in two studies and was 76.1% [62] according to the consensus definition of the Asian working group for sarcopenia and 40% (34% men, 46% women) [73] according to reduced fat-free mass index and quadriceps strength. Prevalence of frailty according to Fried was reported in one study [39]; 14.8% were frail and 55.6% prefrail.…”
Section: Body Composition Sarcopenia and Frailtymentioning
confidence: 97%
“…The prevalence of reduced muscle mass was described only by one study which reported a reduced SMMI (women < 5.4 kg/m 2 , men < 7.0 kg/m 2 ) in 42.3% of women and 57.7% of men [63]. The prevalence of sarcopenia was reported in two studies and was 76.1% [62] according to the consensus definition of the Asian working group for sarcopenia and 40% (34% men, 46% women) [73] according to reduced fat-free mass index and quadriceps strength. Prevalence of frailty according to Fried was reported in one study [39]; 14.8% were frail and 55.6% prefrail.…”
Section: Body Composition Sarcopenia and Frailtymentioning
confidence: 97%
“…Several authors also reported a decline in the strength of the swallowing muscles with aging or sarcopenia [116]. Maximal tongue strength decreases with aging [116][117][118][119], and there is some evidence that aging leads to a decreased jaw-opening force in older men. Several authors also reported an association between tongue strength and handgrip strength [120,121].…”
Section: Sarcopenia and Oral Statusmentioning
confidence: 99%
“…Grip strength and walking speed are associated with tongue pressure and to a lesser extent jaw opening force in men (62)(63)(64)(65)(66)(67)(68). Similarly, head lifting strength is associated with dysphagia and malnutrition in older persons (69).…”
Section: The Frailty Phenotype and Dysphagiamentioning
confidence: 99%